Impact of 18F‐fluorodeoxyglucose (FDG)‐positron‐emission tomography/computed tomography (PET/CT) on management of patients with carcinoma invading bladder muscle. (24th June 2013) - Mertens, Laura S.; Fioole‐Bruining, Annemarie; Vegt, Erik; Vogel, Wouter V.; van, Bas W.; Horenblas, Simon
<x xml:space="preserve">Abstract</x> Objective To evaluate the clinical impact of 18F‐fluorodeoxyglucose (FDG)‐positron‐emission tomography/computed tomography (PET/CT) scanning, compared with conventional staging with contrast‐enhanced CT imaging (CECT). Patients and Methods The FDG‐PET/CT results of 96 consecutive patients with bladder cancer were analysed. Patients included in this study underwent standard CECT imaging of the chest and abdomen/pelvis <4 weeks before FDG‐PET/CT. Based on the original imaging reports and recorded tumour stage before and after FDG‐PET/CT imaging, the preferred treatment strategies before FDG‐PET/CT and after FDG‐PET/CT were determined for each patient using an institutional multidisciplinary guideline. One of the following treatment strategies was chosen: (i) local curative treatment; (ii) neoadjuvant/induction chemotherapy; or (iii) palliation. The changes in management decisions before and after FDG‐PET/CT were assessed. Results The median (range) interval between CECT and FDG‐PET/CT was 0 (029) days. In 21.9% of the patients, stage on FDG‐PET/CT and CECT were different. Upstaging by FDG‐PET/CT was more frequent than downstaging (19.8 vs 2.1%). Clinical management changed for 13.5% of patients as a result of FDG‐PET/CT upstaging. In eight patients, FDG‐PET/CT detected second primary tumours. This led to changes of bladder cancer treatment in another four of 96 patients (4.2%). All the management changes were validated by tissue confirmation of the additional lesions. Conclusions FDG‐PET/CT provides important additional staging information, which influences the treatment of carcinoma invading bladder muscle in almost 20% of cases. Patient selection for neoadjuvant/induction chemotherapy was improved and futile attempts at curative treatment in patients found to have metastases were avoided.